1981
DOI: 10.1159/000120000
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Arteriovenous Malformations in Children (56 Cases)

Abstract: A survey of 56 patients aged ≤ 16 years, admitted (1954–1979) for cerebral arteriovenous malformations, is presented. The clinical manifestation was mostly related to hemorrhage, less frequently to epilepsy or to a cerebral ‘steal’ syndrome. The most frequent site was the parietal lobe, with supply from the middle cerebral artery. Deep malformations were not uncommon and most lesions were of medium or large size. 38 patients were operated upon, and 18 were given treatment other than surgical (including radioth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0
2

Year Published

1986
1986
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 13 publications
4
28
0
2
Order By: Relevance
“…1,3,4,14,23,39 Pediatric patients with AVMs are more likely to present with hemorrhage than adults. 2,5,10,11 The annual risk of hemorrhage for untreated AVMs has been estimated to be 2%-4%, a mortality rate of 5%-10% after hemorrhage, and a 50% risk of severe morbidity associated with hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,3,4,14,23,39 Pediatric patients with AVMs are more likely to present with hemorrhage than adults. 2,5,10,11 The annual risk of hemorrhage for untreated AVMs has been estimated to be 2%-4%, a mortality rate of 5%-10% after hemorrhage, and a 50% risk of severe morbidity associated with hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…2,5,11 Several authors report that an initial hemorrhagic presentation varies from 38% to 45% of their patients. 7,40 In the present study, 64% of our pediatric patients with AVMs had a history of hemorrhage.…”
Section: Hemorrhage After Srsmentioning
confidence: 99%
“…In 15% to 30% of the cases, seizures are the first clinical manifestations. 11,12 A relationship between the type of initial presentation and the size of the AVM has been described, the small AVMs manifesting themselves by strokes and the large ones by seizure. 1 Deeply comatose children could represent 50% of the cases in the particular entity of cerebellar hemorrhages.…”
Section: Discussionmentioning
confidence: 99%
“…There is a high propensity (80%) for the AVM childhood to present bleeding 8 , what is higher than that reported for adults 9,[15][16][17] . Likewise, epilepsy was reported in 12-18%of the AVM` s children series 7,18 and in 16 to 53% of the adult patients 19,20 . In neonates, AVM has been recognized as a cause of life-threatening congestive heart failure 21 .…”
Section: Discussionmentioning
confidence: 92%
“…Several authors have reported that the prognosis was not so good in children with AVM in comparison to adults 7,18,22 . Conversely, a better prognosis was suggested for purely intraventricular haemorrhage arteriovenous malformation as observed in our patient by some reports 23 .…”
Section: Discussionmentioning
confidence: 96%